(untitled) (Proceedings of Southern Federal University. Philology, 2020)
The paper presents the results of research on the potential of news articles and their online user comments as a linguistic material for the disciplines of the philological cycle that study the situational features of the language usage and its cultural component such as the National and Cultural Specifics of Modern Mass Media, Principles of Building Discourse, Country through Language Studies, Contrastive Analysis of Languages and Cultures, Similarities and Differences in Languages, etc. It also provides ways to search for authentic sources using advanced Google search and corpora; exercise options for independent work and assignments in groups are offered. Key words: master’s degree program, foreign language, news articles, online comments, cultural linguistics, exercise options. DOI 10.18522/1995-0640-2020-2-198-205